Konseling Kelompok Teknik Behavioral Contract dalam Menurunkan Intensitas Bermain Game Online Pada Siswa - Nadia Maulita; Barriyati Barriyati; Randi Saputra (An-Nadwah, 2023)
Online game is a game that is favored by all age groups, especially to students. However, the high intensity of playing online games can have a bad influence on students life. This study aims to overcome this problem by reducing the high intensity of playing online games for students. Using the Counseling Guidance Action Research (PTBK) method, researchers provided services in the form of group counseling using behavioral contract techniques to reduce the intensity of playing online games for grade X MIPA 1 students for the 2022/2023 school year at MAN Landak. The data collection techniques used were questionnaires on the intensity scale of playing online games, interviews, observations, and reflection journals. Data analysis techniques in this study used quantitative data analysis techniques questionnaires and qualitative data analysis of Miles and Huberman. The results of this study showed a decrease in cycle 1, namely 9 students from a high scale changing to a low scale and 1 student from a high scale to a low scale with a percentage decrease in the intensity of playing online games in cycle 1 as much as 21%. Next in cycle 2 as many as showing 7 students in the medium category and 3 students in the low category with a percentage decrease in the intensity of playing online games as  much as 6%. This shows that group counseling using behavioral contract techniques can reduce the intensity of playing online games in grade X MIPA 1 students for the 2022/2023 school year at MAN Landak.